Basic Symptoms Are Associated With Age in Patients With a Clinical High-Risk State for Psychosis: Results From the PRONIA Study - Walger, Helene; Antonucci, Linda A.; Pigoni, Alessandro; Upthegrove, Rachel; Salokangas, Raimo K. R.; Lencer, Rebekka; Chisholm, Katharine; Riecher-Rössler, Anita; Haidl, Theresa; Meisenzahl, Eva; Rosen, Marlene; Ruhrmann, Stephan; et al. (Frontiers in Psychiatry, 2020)
In community studies, both attenuated psychotic symptoms (APS) and basic symptoms (BS) were more frequent but less clinically relevant in children and adolescents compared to adults. In doing so, they displayed differential age thresholds that were around age 16 for APS, around age 18 for perceptive BS, and within the early twenties for cognitive BS. Only the age effect has previously been studied and replicated in clinical samples for APS. Thus, we examined the reported age effect on and age thresholds of 14 criteria-relevant BS in a patient sample at clinical-high risk of psychosis (N=261, age 15-40 yrs.), recruited within the European multicenter PRONIA-study. BS and the BS criteria, ‘Cognitive Disturbances’ (COGDIS ) and ‘Cognitive-perceptive BS’ (COPER), were assessed with the ‘Schizophrenia Proneness Instrument, Adult version’ (SPI-A). Using logistic regressions, prevalence rates of perceptive and cognitive BS, and of COGDIS and COPER, as well as the impact of social and role functioning on the association between age and BS were studied in three age groups (15-18 yrs., 19-23 yrs., 24-40 yrs.). Most patients (91.2%) reported any BS, 55.9% any perceptive and 87.4% any cognitive BS. Furthermore, 56.3% met COGDIS and 80.5% COPER. Not exhibiting the reported differential age thresholds, both perceptive and cognitive BS, and, at trend level only, COPER were less prevalent in the oldest age group (24-40 yrs.); COGDIS was most frequent in the youngest group (15-18 yrs.). Functional deficits did not better explain the association with age, particularly in perceptive BS and cognitive BS meeting the frequency requirement of BS criteria. Our findings broadly confirmed an age threshold in BS and, thus, the earlier assumed link between presence of BS and brain maturation processes. Yet, age thresholds of perceptive and cognitive BS did not differ. This lack of differential age thresholds might be due to more pronounced the brain abnormalities in this clinical sample compared to earlier community samples. These might have also shown in more frequently occurring and persistent BS that, however, also resulted from a sampling towards these, i.e., towards COGDIS. Future studies should address the neurobiological basis of CHR criteria in relation to age.